The splicing factor U1-70K interacts with the SMN complex and is required for nuclear gem integrity - Stejskalová, Eva; Staněk, David (Journal of cell science, 2014)
The nuclear SMN complex localizes to specific structures called nuclear gems. The loss of gems is a cellular marker for several neurodegenerative diseases. Here, we identify that the U1-snRNP-specific protein U1-70K localizes to nuclear gems, and we show that U1-70K is necessary for gem integrity. Furthermore, we show that the interaction between U1-70K and the SMN complex is RNA independent, and we map the SMN complex binding site to the unstructured N-terminal tail of U1-70K. Consistent with these results, the expression of the U1-70K N-terminal tail rescues gem formation. These findings show that U1-70K is an SMN-complex-associating protein, and they suggest a new function for U1-70K in the formation of nuclear gems.
Keywords: proteinový komplex SMN; Cajal bodies; transport proteinů; sestřih RNA; Humans; HeLa buňky; U1 snRNP; Cell Nucleus; Protein Transport; Protein Binding; SMN Complex Proteins; Nuclear structure; vazebná místa; lidé; buněčné jádro; malý jaderný ribonukleoprotein U1; Binding Sites; SMN; asociované struktury Cajalových tělísek; Ribonucleoprotein, U1 Small Nuclear; U1-70K; HeLa Cells; Gemini of Coiled Bodies; vazba proteinů; RNA Splicing; Gems